A rapid microwave initiated polyol synthesis of cerium oxide nanoparticle using different cerium precursors. Issue 6 (July 2015) - Soren, Siba; Bessoi, Monalisa; Parhi, Purnendu
Abstract: Single phase cerium Oxide (CeO2 ) nanoparticles have been synthesized by the microwave mediated polyol method in just 10 min. Synthesis of cerium oxide nanoparticle has been attempted using different cerium precursors such as ceric ammonium nitrate, ceric chloride, ceric nitrate, ceric sulfate and ceric ammonium sulfate. Effect of precursor on the synthesis of cerium oxide nanoparticle has been evaluated. The as-synthesized products were characterized by powder X-ray diffraction (XRD), transmission electron microscopy (TEM), scanning electron microscopy (SEM) and Fourier transform infrared spectroscopy (FT-IR).